2020
DOI: 10.1007/s00063-020-00658-3
|View full text |Cite
|
Sign up to set email alerts
|

Options in extracorporeal support of multiple organ failure

Abstract: Considering the invasiveness and risks of high-flow ECMO, Gattinoni and coworkers introduced the concept of less invasive extracorporeal lung support restricted to CO2 removal (ECCO2R) [23]. With a more limited blood flow, ECCO2R technologies are intriguing for combination with other ECOS devices, in particular with RRT. As shown in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 59 publications
(41 reference statements)
0
25
0
1
Order By: Relevance
“…Huber recently reported ADVOS to be “the first integrated MOST device” (MOST = multiple organ support therapy). [ 32 ] In this review, they were highlighted the specific features of the “intelligent” dialysate of ADVOS, which can be adapted to the patient needs, allowing a correction of acid-base imbalances, including CO 2 removal. [ 20 , 21 ] A recent publication from his group reported a median CO 2 removal of 48 ml/minutes in a COVID-19 patient with multiple organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…Huber recently reported ADVOS to be “the first integrated MOST device” (MOST = multiple organ support therapy). [ 32 ] In this review, they were highlighted the specific features of the “intelligent” dialysate of ADVOS, which can be adapted to the patient needs, allowing a correction of acid-base imbalances, including CO 2 removal. [ 20 , 21 ] A recent publication from his group reported a median CO 2 removal of 48 ml/minutes in a COVID-19 patient with multiple organ failure.…”
Section: Discussionmentioning
confidence: 99%
“…During the late 1990s and the 2000s, marketing of extracorporeal liver support systems to eliminate protein‐bound toxins began. These include albumin dialysis therapies such as single‐pass albumin dialysis (SPAD) and the Molecular Adsorbent Recirculating System (MARS®), the fractionized plasma separation and adsorption system (Prometheus®), high‐volume plasma exchange (HVP), extracorporeal bioartificial cellular therapies using extracorporeal liver cell bioreactors for blood purification and more recently, hemadsorption 7 . Initial clinical studies demonstrated multiple benefits, although the results of subsequent randomized clinical trials reduced the initial euphoria 8 .…”
Section: Introductionmentioning
confidence: 99%
“…These single‐organ support devices may be implemented as and when required to support failing organ systems and are familiar to the intensive care staff accustomed to their daily use. However, the use of multiple single‐organ support devices can mandate a large extra‐corporeal volume, is cumbersome, requires additional time for their set‐up and maintenance, and is associated with significant financial implications 7 . This being said, many authors point toward a multiple organ support therapy (MOST), which would integrate several single‐organ support systems into one device 15–17 to limit extra‐corporeal blood volume and reduce operator effort.…”
Section: Introductionmentioning
confidence: 99%
“…Munich, Germany) system, is an albumin hemodialysis approach for elimination of water-soluble and protein-bound toxins, CO 2 removal and acid-base balance control. 7 9 A combination of multiple organ support (i.e. kidney, liver, lung) and of low invasiveness (blood flow 10-times lower than ECMO; need for conventional dialysis catheter; absence of gas phase), make ADVOS a promising approach for patients with multiple organ failure, including those with severe COVID-19.…”
Section: Introductionmentioning
confidence: 99%